1983
DOI: 10.1017/s0033291700050923
|View full text |Cite
|
Sign up to set email alerts
|

Functional visual loss: I. A true psuchiatric disorder?

Abstract: SYNOPSISA review of the literature describing patients with functional visual loss reveals that a significant proportion of them do not manifest psychiatric disease as defined by current nomenclature. Apparently, these individuals are highly suggestible and do not necessarily have psychological pathology. The ramifications of this finding are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 54 publications
0
40
0
4
Order By: Relevance
“…In common with other authors, we have found that at least 60% of our patients do not appear to have any psychiatric morbidity that might account for their symptoms. 16 This does not fit with the conversion or hysterical model of unexplained medical symptoms. We may have underestimated the prevalence of psychiatric morbidity as our criterion was whether the patients were receiving or had received anxiolytics or psychotropic medication or had been under the care of a psychiatrist in the recent past.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In common with other authors, we have found that at least 60% of our patients do not appear to have any psychiatric morbidity that might account for their symptoms. 16 This does not fit with the conversion or hysterical model of unexplained medical symptoms. We may have underestimated the prevalence of psychiatric morbidity as our criterion was whether the patients were receiving or had received anxiolytics or psychotropic medication or had been under the care of a psychiatrist in the recent past.…”
Section: Discussionmentioning
confidence: 93%
“…16,17 Evidence of suggestibility can sometimes be seen on examination. For example, by suggesting that the earlier plates of the Ishihara pseudoisochromatic test were more difficult than the later plates, three patients could be induced to read the last six plates correctly but not the first contrast plate.…”
Section: Discussionmentioning
confidence: 99%
“…8 Of 42 patients with psychogenic or feigned visual complaints assessed by a psychiatrist in the series reported by Kathol et al, 22 (52%) were found to have psychiatric syndromes. 9 In the above mentioned case a comorbid moderate depressive episode with panic attacks were found , which definitely required psychiatric intervention for symptom relief. However the findings of one case cannot be generalized to all cases of NOVL/Psychogenic blindness.…”
Section: Discussionmentioning
confidence: 93%
“…However, the cornerstone of management for psychogenic or feigned visual complaints remains reassurance by a concerned physician that there is no brain or eye disease. 7 The natural history of non-organic visual loss should be explained and the expectation of complete visual recovery should be expressed. Use of placebo treatments such as eye drops, orthoptic exercises or spectacles are not recommended as they will only serve to undermine the reassurance.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation